Research on the role of classroom language as a mediating tool in knowledge building in english as a foreign language - Salaberri Ramiro, Sagrario (Revista Minerva, 2022)
Even though there is agreement in the research community about the importance of oral language in educational processes, there is not clear agreement on the best way to analyse and study it. Sometimes, classroom language has been examined as a code, investigating formal and structural characteristics while in other occasions patterns for social interaction and communication rules in the classroom have been analysed or the relationship between classroom talk and students’ learning. The starting point in this research and the presentation of results is the conviction that teaching and learning processes are interactive and communicative situations in which educators help learners in a planned and systematic form to build knowledge and that classroom language is one of the most powerful instruments to help in that task. We are interested in the connection between classroom talk and teaching/ learning, between social interaction at the inter-psychological level and individual progression at the intra-psychological level. In conclusion, we are interested in discourse al mediator in the teaching and learning process, understanding learning as a communicative process that takes place in a particular social and cultural scenario.
Keywords: classroom language; knowledge and meaning building; interactive teaching and learning; discourse as mediation; communication and mediation; meaningful learning